It is f + 29919, an expression which cannot be further simplified, nor evaluated.
There cannot be an answer since there is no equation or inequality. The expression can be simplified to -6f -6 or -6(f + 1)
Do you mean F = abc + abc + ac + bc + abc' ? *x+x = x F = abc + ac + bc + abc' *Rearranging F = abc + abc' + ab + bc *Factoring out ab F = ab(c+c') + ab + bc *x+x' = 1 F = ab + ab + bc *x+x = x F = bc
It is not possible to find the expression of 2y if f(x) = 2x - 3x.
9
It is the expression: 342 + f + r
Denoting ff as f2 etc, f2 + f + f3 + f = f3 + f2 + 2f
If 14e + 10f = 12f, the first step towards simplifying the expression is subtracting 10f from each side. You therefore have 14e = 2f, which you can divide by 2 to isolate f. Solution: 7e = f
It is f + 29919, an expression which cannot be further simplified, nor evaluated.
Well, let's take a moment to appreciate these lovely variables, f and g. To simplify this expression, we can combine like terms. So, when we combine the terms with f, we get 5f - 7f + 3f, which simplifies to f. And when we combine the terms with g, we get -3g - 4g, which simplifies to -7g. So, the simplified expression is f - 7g. Remember, there are no mistakes in math, just happy little accidents.
It is an expression and can be simplified to: 3d+f+1
There cannot be an answer since there is no equation or inequality. The expression can be simplified to -6f -6 or -6(f + 1)
That's going to depend on the values of 'a', 'b', 'c', and 'f'.
Substitute the value 3 for x in the expression for f(x) and then calculate its value.
This algebra expression can be simplified to:: -21f2-19f++10
It is 5*f where f is an expression.
To solve functions f ◦ g and g ◦ f: For f ◦ g, first find g(x) and then substitute it into f(x). For g ◦ f, first find f(x) and then substitute it into g(x). Simplify the resulting expression to get the final answer.